Immune mediating molecules and pathogenesis of COVID-19-associated neurological disease. (September 2021) - Singh, HariOm; Singh, Amita; Khan, Abdul Arif; Gupta, Vivek
Abstract: Background: Long period of SARS-CoV-2 infection has been associated with psychiatric and cognitive disorders in adolescents and children. SARS-CoV-2 remains dormant in the CNS leading to neurological complications. The wide expression of ACE2 in the brain raises concern for its involvement in SARS-CoV-2 infection. Though, the mechanistic insights about blood-brain barriers (BBB) crossing by SARS-CoV-2 and further brain infection are still not clear. Moreover, the mechanism behind dormant SARS-CoV-2 infections leading to chronic neurological disorders needs to be unveiled. There is an urgent need to find out the risk factor involved in COVID-19-associated neurological disease. Therefore, the role of immune-associated genes in the pathogenesis of COVID-19 associated neurological diseases is presented which could contribute to finding associated genetic risk factors. Method: The search utilizing multiple databases, specifically, EMBASE, PubMed (Medline), and Google Scholar was performed. Moreover, the literature survey on the involvement of COVID-19, neuropathogenesis, and its consequences was done. Description: Persistent inflammatory stimuli may promote the progression of neurodegenerative diseases. An increased expression level of cytokine, chemokine, and decreased expression level of immune cells has been associated with the COVID-19 patient. Cytokine storm was observed in severe COVID-19 patients. The nature of SARS-CoV-2 infection can be neuroinflammatory. Genes of immune response could be associated with neurodegenerative diseases. Conclusion: The present review will provide a useful framework and help in understanding COVID - 19 - associated neuropathogenesis. Experimental studies on immune-associated genes in COVID-19 patients with neurological manifestations could be helpful to establish its neuropathogenesis. Highlights: This review provides a useful insight and framework to understand COVID - 19 - associated neuropathogenesis. Present text could be helpful to identify the susceptible cell types for SARS-CoV-2 infection. This text provides better understanding of altered smell perception in COVID-19 disease. Expression studies can be designed based on this text for better understanding of neuropathogenesis caused by COVID-19. Evaluation of cognitive, psychiatric and virological data from patients surviving severe COVID-19 is warranted.